Using SDN as a Technology Enabler for Distance Learning Applications - Zahra Al-Abri; Ahmed Al Maashri; Dawood Al-Abri; Fahad Bait Shiginah (IAES Indonesian Section, 2018)
The number of students who obtained degrees via distance learning has grown considerably in the last few years. Services provided by distance learning systems are expected to be delivered in a fast and reliable way. However, as the number of users increases, so does the stress on the network. Software-Defined Networking, on the other hand, is a new technology that provides a rapid response to the ever-evolving requirements of today’s businesses. The technology is expected to enhance the overall performance of cloud services, including those provided by distance learning. This paper investigates the benefits of employing such a technology by educational institutions to provide quality services to the users. The results of the experiments show an improvement in performance of up to 11%, when utilizing the technology. In addition, we show how resource reservation features can be utilized to provide quality service to users depending on their role in the distance learning system.